2010
DOI: 10.5897/ajbx09.071
|View full text |Cite
|
Sign up to set email alerts
|

Prospective of biodiesel production utilizing microalgae as the cell factories: A comprehensive discussion

Abstract: Microalgae are sunlight-driven miniature factories that convert atmospheric CO 2 to polar and neutral lipids which after esterification can be utilized as an alternative source of petroleum. Further, other metabolic products such as bioethanol and biohydrogen produced by algal cells are also being considered for the same purpose. Microaglae are more efficient than the conventional oleaginous plants in capturing solar energy as they have simpler cellular organization and high capacity to produce lipids even und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…This treatment had no additions of molasses, favouring conditions of autotrophic (Avnimelech, 2009). The different C/N ratios among treatments make possible the presence of algae for the lowest ratios (10/1) since the microalgae have a great capacity to contribute and produce lipids (Verma et al, 2010), a condition that can explain the difference in lipid percentages between autotrophic and heterotrophic treatments (Becerril-Cortés et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This treatment had no additions of molasses, favouring conditions of autotrophic (Avnimelech, 2009). The different C/N ratios among treatments make possible the presence of algae for the lowest ratios (10/1) since the microalgae have a great capacity to contribute and produce lipids (Verma et al, 2010), a condition that can explain the difference in lipid percentages between autotrophic and heterotrophic treatments (Becerril-Cortés et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered to be the most problematic area of production (Greenwell et al 2010) and as a key factor limiting commercial exploitation of microalgae (Olgu', 2003). It has been suggested that 20-30% of the cost of microalgal biomass is due to harvesting costs (Mata et al 2010;Molina Grima et al 2003;Verma et al 2010). 50% of the biomass cost of microalgae has been reported (Greenwell et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Large demands of environmental friendly glycerol are covered through bio-fuel production which generates glycerol as a by-product [13, 18]. Beyond the high prices and availability fluctuations [19], there are many impurities in biofuel [19], which raise the purification costs as complex purification processes are needed [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, bio-fuel production utilizes enormous agricultural areas necessary to nourish the world population [23, 24]. Therefore, a sustainable and less area-intensive production process for the extensively required raw material glycerol is of great importance [18, 25]. Used cooking oil might be a sustainable alternative for the bio-fuel and glycerol production [26], but also does not reach a glycerol purify higher than 99.7% [22].…”
Section: Introductionmentioning
confidence: 99%